EP785 Does progression free survival (PFS), overall survival (OS) or platinum sensitive interval (PSI) differ in patients undergoing intermediate/high complexity surgery for advanced ovarian cancer (AOC) when treated by primary (PDS) or Interval (IDS) debulking surgery?. (1st November 2019) - Asher, V; Abdul, S; Tou, S; Persic, M; Collins, A; Seneviratne, L; Gomez, D; Glover, O; Bali, A; Phillips, A
Abstract : Introduction/Background: Both CHORUS and EORTC 55971 demonstrated no difference in OS/PFS between PDS OR IDS. However, both trials have been criticised due to low surgical quality. Retrospective reviews have suggested differences in OS/PFS/PFI. Aim: To investigate if PDS or IDS, affects the OS, PFS or PSI in a cohort of AOC patients receiving high quality surgery. Methodology: All patients with AOC treated between 02/2014–01/2019 obtaining complete cytoreduction with intermediate/high surgical complexity. Recurrence was defined on radiological/CA125 findings. Platinum sensitivity was defined according to international standards. Results: 53 patients were identified (32 PDS and 21 IDS) with full recurrence data. No difference was seen in Age or Surgical complexity. 25 patients had recurred (15 PDS and 10 IDS). No difference was seen between groups in OS or PFS. Median survival was not yet reached. 56% were alive at 41months and 52% alive at 48 months in PDS and IDS groups respectively. Median PFS was 20.7 months in both groups. PFI did not differ between PDS or IDS patients. Conclusion: This study supports the findings of previous randomised studies that no difference persists in OS, PFS or PSI in patients undergoing PDS or IDS. Disclosure: Nothing to disclose.